Studi Literatur Pemanfaatan Teknologi Chat GPT dalam Pendidikan - Iriyani, Sri Astuti; Patty, Elyakim N.S; Akbar, Abu Rizal; Idris, Ridwan; Priyudahari, Bhujangga Ayu Putu (Pendidikan Teknologi Informasi Universitas Bumigora, 2023)
The aim of the research is to analyze the development of publications related to the use of GPT Chat technology in the field of education. The research method is a literature study with bibliometric analysis. A total of 919 articles were used from the Google Scholar database. The results of research publications on the use of GPT Chat technology in education have increased from year to year in the 2018-2022 period. The presentation of research development is known to be 2018, namely 1%, 2019 4%, 2020 17%, 2021 33%, and 2022 45%. There are 6 clusters namely cluster 1 (15 items), cluster 2 (14 items), cluster 3 (13 items), cluster 4 (12 items), cluster 5 (10 items), and cluster 6 (6 items). GPT Chat research network mapping in education topics that are often researched are GPT, System and Chatbot, while the topics that become new themes are Xlnet, Elmo, NLP, Deep Learning, and Dialog Response Generation, so that the keywords with the new theme can be used as a reference in do further research.